Inadequate Self-Care Behaviors among Malaysian Diabetic Patients: The Need for Action by Hospital Pharmacists - Ang, Ju-Ying; Leo, Jie-Shi; George, Doris; Chan, Huan-Keat (Journal of Pharmacy Practice and Community Medicine)
Background: Self-care behaviors have been confirmed to be strongly associated with clinical outcomes of diabetes management. Objective: To determine the prevalence and risk factors of inadequate self-care behaviors among the Malaysian patients with type two diabetes mellitus (T2DM) through screening by hospital pharmacists. Methods: A cross-sectional study was undertaken over a nine-month period at a public tertiary care center in Northern Malaysia. Self-care behaviors of 103 patients with T2DM were evaluated using the 16-item Diabetes Self-Management Questionnaire (DSMQ), and the scores were dichotomized to represent “adequate” (≥6 out of 10) and “inadequate” (<6 out of 10) self-care behaviors. The risk factors for inadequate self-care behaviors were identified using logistic regression analysis. Results: The participants recorded a mean DSMQ score of 7.48±1.32, and 16 (15.5%) of them were found to have inadequate self-care behaviors. Among the four subscales assessed, the “Health-Care Use” had the highest score (8.36±1.99), while the “Physical Activity” had the lowest score (6.82±2.56). Patients with a duration of T2DM less than one year (OR: 12.00; 95%CI: 1.80, 80.05; p=0.010) and between six to ten years (OR: 7.11; 95% CI: 1.36, 37.31; p=0.020) were found more likely to have inadequate self-care behaviors, as compared with those with a disease duration greater than 10 years. Conclusion: A noticeable proportion of patients with T2DM in Malaysia had inadequate self-care behaviors, and were found to be associated with the disease duration. This study suggests a more active role for hospital pharmacists in monitoring and improving the diabetes management of patients.
Keywords: Malaysia; Tertiary care centers; Pharmaceutical services; Pharmacists; Self-care; Type 2 diabetes mellitus